Effects of additional colostrum feeding on the levels of protein fractions in calves' serum - Wojtas, Edyta (Array, 2019)
The aim of this study was to investigate the impact of additional colostrum feeding to new born calves on levels of selected serum protein fractions. The study was conducted on a commercial dairy farm. Twenty-four cows of Polish Holstein-Friesian breed and their calves were included in the trial. Chemical composition, the somatic cell count (SCC), the total bacteria count (TBC) and immunoglobulin G (IgG) concentration were determined in colostrum samples. Blood was collected via jugular vein puncture from a total of 24 calves at the 36th hour of life. Total serum protein (TSP), as well as its fractions (albumins, globulins) and IgG concentration were determined. Greater IgG, total protein, albumins and globulins concentrations were found in serum of calves fed colostrum four times compared with three times on the first day of life. It was concluded that increasing the number of colostrum feedings to four times can be beneficial to forming of passive immunity of newborn calves.